Tinjauan Dogmatis tentang Hubungan Dosa dan Penderitaan Serta Implikasinya bagi Jemaat GBKP Batang Serangan - Ginting, Rico; Munthe, Pardomuan (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
The congregation of GBKP Batang Serangan often understands suffering through a doctrinally rigid perspective that assumes every form of suffering is a direct consequence of personal sin. This assumption creates pastoral challenges, as it may lead to stigmatization of those who suffer and obscure the biblical view of God’s grace and love. The purpose of this study is to examine the relationship between sin and suffering within the understanding of the GBKP Batang Serangan congregation, focusing on analyzing congregational perceptions regarding the direct connection between sin and suffering, and its impact on their faith life. This research employs a mixed-methods approach, combining qualitative interviews with five key informants and quantitative data collected from 79 respondents through questionnaires. The findings reveal that although most congregants still associate suffering with sin, they also recognize that righteous individuals may experience suffering. These insights highlight the need for deeper theological formation to help congregants develop a more holistic and biblical understanding of suffering in their spiritual journey.